Prototype of pharmacogenomics software for informed decision-making in Colombia (2024)
Through this project, the aim is to create a pharmacogenomics software prototype that gathers official data and assists medical professionals in making informed decisions regarding the prescription of medications for their patients. Additionally, the goal is to inform doctors about the most common allelic mutations per departmental population in Colombia. Consequently, our aspiration with the prototype is that the software will soon become accessible through a website to the general public, but with a special emphasis on Colombian medical professionals who wish to utilize it to aid in medical decision-making. Following massive data sampling from departmental sources in Colombia, the objective is to generate an analysis based on medication effectiveness to suggest the potential effects based on the patient's genetic information. This is intended to contribute to precision public health in Colombia, enabling doctors to provide more personalized and effective pharmacological treatments to their patients.